Implementasi dan Evaluasi Modul Pembelajaran Ilmu Pendidikan Kedokteran untuk Mahasiswa Kedokteran Tahap Preklinik - Natalia Puspadewi; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: To keep up with current development in medicine, every doctor is demanded to be able to do continuing medical education (CME) after finishing their medical degree. However, health education institutions are responsible to make sure their graduates are able to do so by developing their self regulated learning (SRL) skills. Therefore, we developed a learning module that not only use adult learning approach but also maximizing the teachers’ role in the teaching and learning process by using a programmatic assessment model.Method: The learning activities mostly used SCL approach (62,7%), and were comprised of 8 different learning method. The assessment activities were done by using a combination of assessment method to assess the student’s cognitive, skills, and professional behavior. The student was also asked to do a self evaluation using reflective writing assignment, and each of the student also received 360 degree. Each student was assigned to 1 mentor to guide him/her throughout the course.Results: More than half of the students (52,24%) claimed that they were ‘forced’ to take the course because they didn’t get into their first choice elective block. However, at the end of the block, all of the students had a change of perspective and agreed that this block was interesting and useful for them. Conclusion: The students are able to be independent if we, as teachers, maximized our role as facilitators and mentors, and give the students bigger autonomy in their study.